Developing Project-Based Intermediate Reading Course Textbooks with Local Wisdom of Kerinci Indigenous People - Sari, Mike Nurmalia; Ningsih, Pretty Elisa Ayu (STKIP Pesisir Selatan, 2024)
This research aims to develop culturally and academically relevant teaching materials in the Intermediate Reading course, by addressing the specific needs of students in the cultural context of Kerinci. Through a comprehensive needs analysis involving students, lecturers, and program leaders, the research identified key areas of difficulty, such as understanding complex texts and academic vocabulary. A project-based learning approach was proposed, integrating local themes to increase student engagement and motivation. This research utilizes the Research and Development (R&D) method with the Four-D research model consisting of Define, Design, Development and Disseminate. Findings show that students are more likely to succeed when teaching materials reflect their cultural background and daily experiences. This research contributes to the field of education by providing a framework for creating Intermediate Reading textbooks that are aligned with students' needs, thus promoting a more inclusive and effective learning environment. The novelty of this study lies in its focus on local wisdom and the integration of interactive learning strategies, paving the way for future educational initiatives that aim to promote academic success and cultural appreciation.